Trichlorido-1κ(2) Cl,2κCl-(2,6-dimethylphenolato-2κO)-μ-oxido-bis{1,2(η(5))-2,3,4,5-tetramethyl-1-[4-(trimethylsilyl)phenyl]cyclopentadienyl}dititanium(IV) - Luo, Xuyang (International Union of Crystallography, 2011)
The title dinuclear titanocene, [Ti(2)(C(8)H(9)O)(C(18)H(25)Si)(2)Cl(3)O], contains one Ti atom tetrahedrally coordinated by two Cl atoms, a bridging O atom and the substituted cyclopentadienyl ligand, and another Ti atom tetrahedrally coordinated by a Cl atom, a bridging O atom, the 2,6-dimethylphenolate ligand and the substituted cyclopentadienyl ligand. The bridging O atom lies on a twofold rotation axis.